The effects of training volume and repetition distance on session rating of perceived exertion and internal load in swimmers - Barroso, R.; Salgueiro, D. F.; do Carmo, E. C.; Nakamura, F. Y. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To assess swimmers` session rating of perceived exertion (sRPE) after standardized sets of interval swimming training performed at the same relative intensity but with different total volume and repetition distance. Methods: Thirteen moderately trained swimmers (21.1 ± 1.1 y, 178 ± 6 cm, 74.1 ± 8.3 kg, 100-m freestyle 60.2 ± 2.9 s) performed 4 standardized sets (10 × 100-m, 20 × 100-m, 10 × 200-m, and 5 × 400-m) at the same relative intensity (ie, critical speed), and 1 coach (age 31 y, 7 y coaching experience) rated their efforts. Swimmers` sRPE was assessed 30 min after the training session. Coach sRPE was collected before each training session. Internal load was calculated by multiplying sRPE by session duration. Results: When bouts with the same repetition distance and different volumes (10 × 100-m vs 20 × 100-m) are compared, sRPE and internal load are higher in 20 × 100-m bouts. When maintaining constant volume, sRPE and internal load (20 × 100-m, 10 × 200-m, and 5 × 400-m) are higher only in 5 × 400-m bouts. The coach`s and swimmers` sRPE differed in 10 × 200-m and 5 × 400-m. Conclusions: These results indicate that sRPE in swimming is affected not only by intensity but also by volume and repetition distance. In addition, swimmers` and the coach`s sRPE were different when longer repetition distances were used during training sessions. Therefore, care should be taken when prescribing swimming sessions with longer volume and/or longer repetition distances.